Correlation Between the Audiologic Findings and Tinnitus Disorder - Mondelli, Maria Fernanda Capoani Garcia; Rocha, Alice Borges da (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The correlation between hearing loss with tinnitus can be justified if we consider that this is a tinnitus-causing factor, since the impairments or degenerations on the inner ear and the vestibulocochlear nerve can cause the tinnitus. According to different reports, 85%-96% of patients with tinnitus show some degree of hearing loss.Objective: To correlate the sex, age, degree and type of hearing loss with the tinnitus disorder in patients at the Electronic Devices-related Clinic of Deafness).Method: Retrospective study of exploratory nature in 100 individuals' records duly registered at the Phonoaudiology Clinic of University of São Paulo's Dentistry School in Bauru FOB/USP, by using the THI instrument (Tinnitus Handicap Inventory).Results and Conclusion: Sex, age and degree of hearing loss do not have an influence over the tinnitus disorder, but the hearing loss in tinnitus listeners is progressively bigger according to age and in individual with neurosensorial hearing loss.
Keywords: hearing loss; tinnitus; questionnaires